Perspectiva de movimentação : emigração valadarense e metáforas espaciais - Stabelini, Fabio (2013)
This research is a gathering of meaning lines for the consolidation of an anthropology of the city of Governador Valadares / MG, Brazilian emigration center. The main focus is on the emigrant population of the city that experienced project emigration-to-the-return. The proposal is a more detailed study of the buildings / homes of these returned migrants or return paths. In this way, ethnography then tended to peripheral dynamics, the production of kinship and the prospect of living the new residence. However, even in its historical and geographical features, identified an appreciation of movement idea, physical and social. Thus, I want to give voice to the space with which the valadarenses think their lives. Some of these significant lines will be gathered in a reflection on the drover beans, recurring option in the food court of the city, both in the center as well as in the periphery. To establish a more specific logic, it was necessary to relativize the concept of identity, as a tool to understand the dynamics of moving populations. Moving perspective is the area for which are indicated all the lines presented in this work.